(untitled) (International Journal of Innovative Technologies in Economy, 2018)
Investments are the driving force of any economy. It is also an indicator of the competitiveness of the country’s economy. In this article, the main categories that show the level of investment attractiveness in Ukraine for today are analyzed. The people’s ability to save money from 2012 to 2017 are shown. The dependence of deposit rate, amount of deposit and economic situation are analyzed.